Microstructure and hardness performance of AA6061 aluminium composite using friction stir processing - Marini, C. D.; Fatchurrohman, Nanang (http://icites2018.com/, 2018)
Rice husk ash (RHA) is an industrial waste that has become a potential reinforced material for aluminium matrix composite (AMCs) due to low cost and abundantly available resources. Friction stir processing (FSP) has been introduced as a method to modify surface properties of the metal and alloy including theirs composite as well. The present work reports the production and characterization of AA6061 and AA6061/5 vol% RHA using FSP using parameters rotation speed 1000 rpm and traversed speed 25 mm/min. The microstructure was studied using optical microscopy (OM). A homogenous dispersion of RHA particles was obtained in the composite. No agglomeration or segregation was observed. The produced composite exhibited a fine grain structure. An improvement in hardness profile was observed as AA6061/5 vol% RHA improves in hardness compared to FSPed of AA6061 without reinforcement.